(untitled) (Journal of Training and Development, 2025)
Apprenticeship programs serve as an effective approach to integrating technical education and industry needs, offering tangible benefits for students, employers, and educational institutions. This study explores the challenges and opportunities for industry-school partnerships in establishing and implementing apprenticeship programs in Nepal, focusing on Lumbini Province. The study employs a qualitative, exploratory case study approach, with interviews and focus group discussions involving 30 stakeholders. It assesses challenges, such as limited industry participation, inadequate legislative frameworks, reliance on foreign labor, and weak collaboration between government and industry. Key findings underscore the necessity of raising industry awareness, fostering government-industry partnerships, and establishing clear policies to institutionalize apprenticeship systems. The article identifies opportunities for strengthening partnerships through improved communication, collaboration in curriculum development, and a focus on addressing industry needs along with some existing challenges.